Soil nitrogen drives inverse acclimation of xylem growth cessation to rising temperature in Northern Hemisphere conifers - Yaling Zhang; Jian-Guo Huang; Minhuang Wang; Wenjin Wang; Feiyu Yang; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; et al. (Proceedings of the National Academy of Sciences, 2025)
Controlled experiments suggest that the seasonal build-up of nitrogen (N) limitation constrains the responses of forest autumn phenology to elevated temperatures. Therefore, rising soil N is expected to increase the delaying effects of elevated temperature on the end of the season, i.e., leaf senescence. However, the interactive effects of temperature, soil N, and aridity on xylem autumn phenology remain unknown. We conducted a wide spatial analysis from 75 conifer sites in the Northern Hemisphere and found that rising soil N increases the delaying effects of elevated temperature on the end of xylem cell wall thickening but reduced the delaying effects on the cessation of cell enlargement, especially in humid regions. The contrasting effects of elevated soil N on cell enlargement versus cell wall thickening could affect xylem cell anatomy, thereby induce changes in wood density, and induce a decoupling of stem size growth from photosynthate production. These analyses extend previous findings on forest autumn phenology by systematically investigating the spatial variation in the interactive effects of temperature and soil N on xylem autumn phenology at the cellular scale.